The role of attention and consistency with schema expectation in memory for objects in place - Zulkiply, Norehan; Gardiner, John M. (2007)
The role of attention and consistency with schema expectation in memory for objects in place were examined in one experiment. Forty participants were asked to study a picture of either the graduate student office or the preschool classroom, and either under full attention condition or under divided attention condition. Sixteen stimulus items, half consistent and half inconsistent with schema expectation about the room settings were placed throughout the room. Participants were later given a free recall test, followed by a same-changed recognition memory test immediately after that. The results show that participants remembered better under full attention condition than under divided attention condition. Items inconsistent with schema expectation were better recalled and recognized than items consistent with schema expectation both under full attention and divided attention conditions. These results support the findings on the consistency effect in some previous studies, in which items inconsistent with expectations being better remembered than items consistent with expectations. Importantly, the present study reveals the influence of manipulation of attention on the consistency effect. The results show that consistency effect occurs in both conditions, with a greater effect reported under divided attention condition than under full attention condition. Reducing the participants’ attention has increased the consistency effect.